THE EFFECT OF HALAL LABEL, PRODUCT QUALITY, AND PRICE ON CONSUMER LOYALTY OF CHICKEN MEAT AT GOLDEN SUPERMARKET MANADO - Cellina Grace Rawung; S. L. H. V. Joyce Lapian; Fitty Valdi Arie (Universitas Sam Ratulangi, 2023)
Satisfaction of basic human needs today is one thing that must be met. Fulfillment is not just to receive or consume it, not even just to feel enough and so on, but nowadays there are consumers who are more concerned with other values ​​than just fulfilling them, such as values ​​related to religion.The purpose of this study was to determine the effect of halal label, product quality and price on consumer loyalty of chicken meat at Golden Supermarket Manado either simultaneously or partially on consumer loyalty. The type of research used is associative research with Multiple Linear Regression analysis method. The number of samples used is 100 respondents.The results showed that simultaneously and partially halal label, product quality and price affect consumer loyalty. The management can pay attention to the quality of the product to consumers so that in the future there will be an increase in consumer loyalty for meat ayang at Golden Supermarket Manado. Keywords: halal label, product quality, price, consumer loyalty